2013
DOI: 10.1016/j.humpath.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Calretinin expression in high-grade invasive ductal carcinoma of the breast is associated with basal-like subtype and unfavorable prognosis

Abstract: Calretinin, a calcium-binding protein, is a widely utilized marker for mesothelial differentiation. There is accumulating evidence of calretinin expression in epithelial and mesenchymal malignancies as well. The objectives of this study were 1) further delineate the expression of calretinin in grade 3 breast carcinomas in the context of molecular subtypes and 2) identify the impact of calretinin expression on overall- and disease-free survival. On the basis of immunohistochemical expression of estrogen recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
7
29
0
1
Order By: Relevance
“…More cases should be studied to find the clinical significance of the TNB and TNN and any biomarkers that could predict the clinical outcome other than the ones that we used to classify these two subtypes. Recently calretinin expression had been found to correlate with poor clinical outcome in TNB subtype (Taliano et al, 2013). We did not study this marker in the current study.…”
Section: Discussionmentioning
confidence: 79%
“…More cases should be studied to find the clinical significance of the TNB and TNN and any biomarkers that could predict the clinical outcome other than the ones that we used to classify these two subtypes. Recently calretinin expression had been found to correlate with poor clinical outcome in TNB subtype (Taliano et al, 2013). We did not study this marker in the current study.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, global gene expression analysis in ovarian/peritoneal serous carcinoma (O/P‐SC) versus diffuse peritoneal malignant mesothelioma (DMPM) revealed that CRT was overexpressed in DMPM but not in O/P‐SC, suggesting that CRT could be (along a potential gene‐expression signature) a marker for differentiating DMPM from O/P‐SC . In breast cancer, for comparison, strong CRT expression was predominantly observed in high‐grade tumors with basal‐like phenotypes and paralleled poor prognosis . Moreover, an alternatively spliced form of CRT (CRT‐22k) was detected in serum of breast cancer patients…”
Section: Discussionmentioning
confidence: 99%
“…27 In breast cancer, for comparison, strong CRT expression was predominantly observed in high-grade tumors with basal-like phenotypes and paralleled poor prognosis. 28,29 Moreover, an alternatively spliced form of CRT (CRT-22k) was detected in serum of breast cancer patients. 30 Considering that CRT is also highly expressed in mesothelial cells of the peritoneum, 15,16 it is alternatively possible that elevated sCRT in advanced ovarian cancer patients is related to the tumor microenvironment within peritoneal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin expression has already been reported in normal breast tissues and breast carcinoma [25]. In three studies, this marker was associated to breast carcinoma of worse prognosis, especially of basal-like phenotype [26][27][28].…”
Section: Discussionmentioning
confidence: 99%